Analisis Sosial Media Marketing terhadap Purchase Intention - Hartanto, Prasetyo; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Jurnal Informatika Ekonomi Bisnis, 2022)
The purpose of this study is to analyze the effect of Social Media Marketing on Customer Purchase Intentions. The data used in this study were obtained directly from distributing online. The number of respondents in this study was 115 people. The results of testing the hypothesis in this study indicate that: Firm- Created Social Media Communication has a positive and significant effect on User-Generated Social Media Communication,and Brand Passion. Meanwhile, User-Generated Social Media Communication has no effect on Brand Passion. The results of the study also show that Brand Passion has a positive and significant effect on Brand Loyalty and Purchase Intention. Brand Loyalty also has a positive and significant effect on consumer Purchase Intention. As for the limitations in this study, it only uses one company brand as the object studied, so the results cannot be generalized to coffee shop company brands as a whole and also the selection of respondents is only in Indonesia so it is not can represent the behavior of Starbucks consumers as a whole spread across many countries. Furthermore, this study has not been able to reveal the overall factors that influence purchase intention due to limited variables in this study which are only limited to social media marketing which is divided into two parts; firm-created social media communication and user-generated social media communication, brand passion and brand loyalty so that there are other variables that are not included in this study.